2023
DOI: 10.1242/dmm.049954
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected phenotypic and molecular changes of combined glucocerebrosidase and acid sphingomyelinase deficiency

Abstract: Heterozygous variants in GBA1 encoding glucocerebrosidase (GCase) are the most common genetic risk factor for Parkinson's disease (PD). Moreover, sporadic PD patients also have a substantial reduction of GCase activity. Genetic variants in SMPD1 are also overrepresented in PD cohorts, whilst a reduction of its encoded enzyme (ASM) activity is linked to an earlier age of PD onset. Despite both converging on the ceramide pathway, how combined deficiencies of both enzymes may interact to modulate PD has yet to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The early rise in NFκB and Jak-Stat signaling in the psap KO brain supports pharmacological modulation of these pathways as one strategy toward symptom alleviation. Additionally, given recent evidence of successful Farber and Gaucher disease rescue via acid sphingomyelinase knockout ( Keatinge et al, 2023 ; Beckmann et al, 2019 ), we also examined this genetic rescue strategy for the psap KO model.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The early rise in NFκB and Jak-Stat signaling in the psap KO brain supports pharmacological modulation of these pathways as one strategy toward symptom alleviation. Additionally, given recent evidence of successful Farber and Gaucher disease rescue via acid sphingomyelinase knockout ( Keatinge et al, 2023 ; Beckmann et al, 2019 ), we also examined this genetic rescue strategy for the psap KO model.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to small-molecule-based treatment, a genetic rescue was also explored based on previous reports of successful Farber and Gaucher disease mitigation by crossing the respective mouse and zebrafish models with an acid sphingomyelinase (SMPD1) deficiency model ( Keatinge et al, 2020 preprint; Beckmann et al, 2019 ). In the context of the sphingolipid metabolic pathway, it is possible that SMPD1 knockout-induced ceramide depletion may counter ceramide accumulation in Farber disease and enhance lifespan in the Gaucher model by shifting complex sphingolipid catabolism toward ceramide instead of psychosine.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The zebrafish has shown to be a promising complementary in vivo vertebrate model of neurodegeneration, demonstrating the key markers of pathology, including neuronal loss and gliosis, even during early larval stages, in models of various neurodegenerative conditions 22,[25][26][27][28][29][30][31][32] . Previous studies characterising c9orf72 deficient larval zebrafish utilised a knock down approach with Morpholinos 33 , and indicated that knockdown of c9orf72 in zebrafish resulted in axon outgrowth deficits in motor neurons and reduction in spontaneous movement 33 .…”
Section: Introductionmentioning
confidence: 99%